Molecular Mechanisms of the Floral Biology of Jatropha curcas: Opportunities and Challenges as an Energy Crop - Gangwar, Manali; Shankar, Jata (Frontiers in Plant Science, 2020)
Fossil fuel sources are limited and could eventually be depleted. Biofuels emerge as a renewable alternative to fossil fuels. Jatropha has grown in significance as a potential bioenergy crop due to its high content of seed oil. However, Jatropha's lack of high yielding seed genotypes limits its potential use for biofuel production. The main cause of lower seed yield is the low female to male flower ratio (1:25-10), which affects the total amount of seeds produced per plant. Here, we review the genetic factors responsible for floral transitions, floral organ development, and regulated gene products in Jatropha. We also summarize potential gene targets to increase seed production and discuss challenges ahead.